TANGGUNG JAWAB NOTARIS YANG TIDAK DAPAT MENUNJUKKAN MINUTA AKTA DALAM PROTOKOL NOTARIS PADA PEMERIKSAAN KEPOLISIAN - Gio Vanni Tampubolon; Rr.Dijan Widijowati; Felicitas Sri Marniati (Jurnal Ilmiah Global Education, 2023)
For the purposes of the judicial process, investigators, public prosecutors, or judges with the approval of the Notary Honor Council are authorized to take photocopies of Minutes of Deeds and/or letters attached to Minutes of Deeds or Notary Protocols in the Notary's custody. However, in practice or the phenomena that occur, the notary cannot show the minutes of the deed that should be kept as a notary protocol. The formulation of the problems in this study What are the legal consequences of a notary not being able to show the minutes of the deed during a police inspection? And What is the form of responsibility of a notary who cannot show minutes of the deed during police investigation? The frame of mind in this research uses the theory of responsibility and the theory of legal consequences.This research uses the type of normative juridical research. The research approach used is the statutory approach, the conceptual approach, the analytical approach and the case approach. The sources of legal materials used are primary, secondary and tertiary legal materials. The technique of collecting legal material is carried out by identifying and inventorying positive law, literature, books, journals and other sources of legal materials. The technique of analyzing legal material is carried out by means of grammatical interpretation and systematic The results of the study show that Legal consequences if the Minuta Deed is destroyed but not due to force majeure, the Notary cannot be held responsible. Legal consequences if the minutes of the deed are destroyed due to a notary's mistake or negligence, the notary must be responsible and may be subject to civil and/or administrative sanctions. as stated in Article 9 paragraph (1) letter d UUJN namely temporary dismissal from his position as a Notary because he has violated the obligations and prohibitions of office